Uterine Fibroids: Bridging Genomic Defects and Chronic Inflammation - El Andaloussi, Abdeljabar; Chaudhry, Zuni; Al-Hendy, Ayman; Ismail, Nahed (Seminars in Reproductive Medicine, 2017)
Uterine fibroids (UF; aka leiomyoma, myomas) are the most common benign tumors of female reproductive tract. They are highly prevalent, with 70 to 80% of women burdened by the end of their reproductive years. Fibroids are a leading cause of pelvic pain, abnormal vaginal bleeding, pelvic bulk symptoms, miscarriage, and infertility. They are the leading indication for hysterectomy, and costs exceed 34 billion dollars annually in the United States alone. Recently, somatic mutations in exons 1 and 2 of Med12 gene emerged as common UF driver mutations. Unfortunately, the detailed etiology of UF is not fully realized. Particularly, very little is known about possible dysregulation of inflammatory and immune processes and their possible contribution to UF pathogenesis. The notion on possible impact of altered estrogen and progesterone signaling in UF on inflammatory responses and DNA repair machinery that can conceivably lead to tumor-specific somatic mutation is indeed an intriguing concept which has some foundation in available observation in other hormonally responsive tissues. This review highlights and summarizes our current knowledge on the convergence of such pathways and their relevance for UF pathogenesis.
Keywords: inflammation; progesterone; cytokines; immune cells; Estrogen; Med12